A slow-release polysulfide lightweight material and its preparation method and application
The soluble polysulfide light material is generated by mixing sulfur and cement, which solves the problem of low sulfur solubility and achieves efficient wastewater nitrogen removal and phosphorus removal effects, which is easy to obtain raw materials and low cost.
Patent Information
- Application Number
- CN202311123401.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-08-22
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing sewage treatment technology has low solubility of sulfur, is not easy to use efficiently by microorganisms, and the denitrification rate is limited, making it difficult to meet the water quality standards.
By mixing sulfur with cement, a cement slurry is formed and foamed, and it is allowed to stand and solidify at high temperature to form a soluble polysulfide light material. The alkaline substances generated by the cement hydration reaction react with sulfur to form a soluble polysulfide. As an electron donor for autotrophic denitrification, combined with the synergistic effect of pyrote, the denitrification rate is increased.
The denitrification rate of sewage treatment has been greatly improved, the specific surface area of the material and the amount of microbial adhesion have been enhanced, and high-efficiency nitrogen removal has been achieved, which is easy to obtain raw materials and is cheap.
Smart Images

Figure CN117069257B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental functional materials and sewage treatment, and more specifically, relates to a slow-release polysulfide lightweight material and a preparation method and application thereof. Background Art
[0002] With the rapid development of my country's socioeconomic landscape, particularly the accelerated pace of urbanization, large quantities of industrial and domestic wastewater have been discharged. Nutrients such as nitrogen and phosphorus have entered water bodies, leading to eutrophication. Furthermore, the discharge of industrial wastewater and waste residues has caused a significant influx of heavy metals into the soil, leading to excessive levels of heavy metals in the soil. To control water and soil pollution, the government has invested heavily in the construction of wastewater and waste residue treatment facilities.
[0003] At present, sewage treatment methods are roughly divided into physical, chemical and biological methods. In the actual sewage treatment process, multiple methods are often used in combination to improve the treatment effect. Compared with heterotrophic denitrification, sulfur autotrophic denitrification has the characteristics of low energy consumption, low cost and excellent effect in removing nutrients from water. It has been increasingly widely used in recent years. With the continuous deepening of research, the synergistic effect caused by the mutual reaction between different materials has also received more and more attention. For example, the most commonly used sulfur / limestone autotrophic denitrification system (SLAD) can simultaneously remove nitrogen, phosphorus and other pollutants from sewage. However, sulfur itself is difficult to dissolve in water, and its biological utilization has certain limitations. In addition, the phosphorus removal effect of this system is limited, making it difficult to meet the water quality standards after improvement.
[0004] After searching, the patent application document with patent application number 201811034113.8 discloses a coupled filler autotrophic denitrification biological filter. This invention uses pyrrhotite and sulfur for autotrophic denitrification to remove pollutants such as nitrogen and phosphorus from water. This invention improves the denitrification rate through the synergistic effect of sulfur and pyrite. However, due to the large particle size of the sulfur source and pyrite particles used, the synergistic effect between sulfur and pyrite is not fully exerted, and the denitrification rate cannot fully meet the needs of practical applications. To this end, the patent application document with patent application number 201910326701.7 discloses a lightweight slow-release denitrification and phosphorus removal material. This invention prepares the material by mixing cement, pyrite and a foaming agent and foaming. The prepared material has the advantages of high specific surface area, controllable density, and easy microbial biofilm formation. However, since it only uses pyrite as the autotrophic denitrification raw material, the autotrophic denitrification rate is low.
[0005] In addition, the patent application document with patent application number 201910329881.4 discloses a lightweight material for simultaneous denitrification and phosphorus removal. The invention mixes sulfur, pyrite and calcium magnesium carbonate and heats them into a molten mixture, foams them and then cools and forms them into a lightweight material. The material is in the form of a molten mixture, which makes the material mixing more uniform, and the synergistic effect of pyrite and sulfur autotrophic denitrification is more obvious, but during the application process, the denitrification rate is still limited by the solubility of sulfur and pyrite. Therefore, there is an urgent need for a low-cost, low-risk, and high-efficiency material for removing pollutants such as nitrogen and phosphorus from water. Summary of the Invention
[0006] 1. Problem to be solved
[0007] To address the low solubility of sulfur in existing sewage treatment technologies, which hinders efficient microbial utilization and limits denitrification rates, the present invention provides a slow-release polysulfide lightweight material, its preparation method, and its application. First, sulfur is mixed with cement, water is added to form a cement slurry, and foaming is performed. Alkali generated during cement hydration reacts with sulfur at high temperature to form soluble polysulfides, resulting in the slow-release polysulfide lightweight material. When this material is used in sewage treatment, the polysulfides are slowly released and, together with sulfur, act as electron donors for autotrophic denitrification, significantly increasing the denitrification rate.
[0008] 2. Technical solution
[0009] In order to solve the above problems, the technical solutions adopted by the present invention are as follows:
[0010] The present invention provides a method for preparing a slow-release polysulfide lightweight material, comprising mixing sulfur and cement to obtain a dry-mix mortar; then adding water to the dry-mix mortar, stirring to obtain a cement slurry, and foaming the cement slurry to obtain a foamed slurry; allowing the foamed slurry to stand and solidify under high temperature conditions, and curing under the same temperature conditions to obtain a slow-release polysulfide lightweight material.
[0011] Preferably, the high temperature condition is 40°C to 100°C; more preferably, 60°C to 80°C.
[0012] Preferably, the curing time is 10 to 20 days.
[0013] Preferably, during the curing process, the humidity of the curing environment is not less than 80%; more preferably, not less than 90%.
[0014] Preferably, the mass ratio of sulfur to cement is (5-25):(50-90).
[0015] Preferably, the mass ratio of the dry-mix mortar to water is 1:(0.3-0.6); more preferably, the mass ratio of the dry-mix mortar to water is 1:(0.45-0.55).
[0016] Preferably, the particle size of the sulfur is ≤0.3 mm; more preferably, the particle size of the sulfur is ≤0.15 mm.
[0017] Preferably, the foaming treatment includes chemical foaming treatment or physical foaming treatment, the chemical foaming treatment uses a chemical foaming agent, wherein the chemical foaming agent is one or both of sodium percarbonate and hydrogen peroxide; the physical foaming treatment uses physical foam, wherein the physical foam is prepared by a 5% to 15% plant protein type foaming agent aqueous solution through a foaming device, and the foaming parameters in the foaming device are set to a gas-water ratio of air to the plant protein type foaming agent aqueous solution of 1: (0.5 to 1.5).
[0018] Preferably, when chemical foaming treatment is performed, the mass ratio of the chemical foaming agent used to the cement slurry is 1% to 10%; more preferably, the amount of the chemical foaming agent added is 1% to 3% sodium percarbonate or 1% to 3% hydrogen peroxide or 8% to 10% sodium bicarbonate.
[0019] Preferably, when performing physical foaming treatment, the amount of physical foam added per ton of cement slurry is 100-500 L, more preferably 200-300 L.
[0020] Preferably, the method for preparing a slow-release polysulfide lightweight material of the present invention comprises adding carbonate minerals to the dry-mix mortar before adding water, and the mass ratio of sulfur, cement, and carbonate minerals is (5-25):(50-90):(50-15).
[0021] Preferably, the carbonate mineral is one or more of limestone (CaCO3), magnesite (MgCO3), dolomite (CaMg(CO3)2), and siderite (FeCO3).
[0022] Preferably, the particle size of the carbonate mineral is ≤0.3 mm.
[0023] More preferably, the method for preparing a slow-release polysulfide lightweight material of the present invention further includes adding pyrite to the dry-mix mortar before adding water, and the mass ratio between the pyrite and the dry-mix mortar is (5-25):100.
[0024] Preferably, the particle size of the pyrite is ≤0.3 mm; more preferably, the particle size of the pyrite is ≤0.15 mm.
[0025] The slow-release polysulfide lightweight material of the present invention is prepared by the above-mentioned preparation method, wherein the slow-release polysulfide lightweight material has a compressive strength of 0.5 to 20 MPa and a density of 0.6 to 1.5 g / cm 3 The porosity is 20% to 70%, and the pore diameter is 0.05 to 1 mm.
[0026] The invention discloses a method for denitrifying and removing phosphorus from sewage by using a slow-release polysulfide lightweight material, comprising: filling the slow-release polysulfide lightweight material into a reactor, inoculating microorganisms to form biofilms, and after biofilm formation, introducing sewage into the reactor to carry out denitrification and dephosphorization treatment.
[0027] Preferably, in the reactor, the slow-release polysulfide lightweight material continuously releases polysulfide into the sewage, and the microorganisms perform autotrophic denitrification and denitrification by utilizing the polysulfide, elemental sulfur and / or pyrite in the slow-release polysulfide lightweight material in the reactor; and the slow-release polysulfide lightweight material continuously releases calcium ions and iron ions into the sewage, and the calcium ions and iron ions react with phosphorus in the water body to generate phosphate precipitation for phosphorus removal.
[0028] 3. Beneficial effects
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention provides a method for preparing a slow-release polysulfide lightweight material. Sulfur and cement are mixed and water is added. Calcium hydroxide, an alkaline substance produced by the cement hydration reaction, undergoes a disproportionation reaction with sulfur at high temperature to produce soluble calcium polysulfide. This overcomes the limitation of sulfur itself being difficult to dissolve in water. Calcium polysulfide is used together with sulfur as an electron donor for autotrophic denitrification to remove nitrogen, thereby significantly improving the wastewater treatment efficiency.
[0031] (2) The slow-release polysulfide lightweight material of the present invention is treated by chemical foaming or physical foaming to uniformly disperse bubbles in the material, so that the material has a dispersed and uniform pore structure after solidification, which greatly increases the specific surface area of the material and makes it easier for microorganisms to attach. The amount of microbial attachment is increased, thereby further improving the removal efficiency of nitrogen and phosphorus pollutants in water;
[0032] (3) A slow-release polysulfide lightweight material of the present invention, due to the disproportionation reaction between calcium hydroxide and sulfur in cement to produce calcium polysulfide, makes calcium ions more soluble in water, and the material continuously releases calcium ions to react with phosphorus in sewage to form phosphate precipitates to achieve the purpose of phosphorus removal;
[0033] (4) The slow-release polysulfide lightweight material of the present invention is made of cement, sulfur or cement, sulfur and pyrite, which are all common industrial products or raw materials. The raw materials are easy to obtain and low in cost. It can be used as artificial wetland filler, sewage treatment fluidized bed, fixed bed filler, and in-situ and ex-situ purification material for polluted water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 (a)-1(b) are a photograph (a) and an electron microscope image (b) of a slow-release polysulfide lightweight material of Example 1;
[0035] Figure 2 This is a diagram showing the polysulfide sustained-release effect of a sustained-release polysulfide lightweight material of Example 1. DETAILED DESCRIPTION
[0036] The present invention will be further described below with reference to specific embodiments.
[0037] The present invention provides a method for preparing a slow-release polysulfide lightweight material, comprising the following steps:
[0038] S10. Mixing sulfur and cement to obtain dry-mix mortar, wherein the mass ratio of sulfur to cement is (5-25):(50-90); the particle size of the sulfur is ≤0.3 mm, preferably, the particle size of the sulfur is ≤0.15 mm;
[0039] S20, adding water to the dry-mix mortar obtained in step S10, stirring evenly to obtain a cement slurry, wherein the mass ratio of the dry-mix mortar to water is 1:(0.3-0.6), preferably, the mass ratio of the dry-mix mortar to water is 1:(0.45-0.55);
[0040] It should be noted that before adding water in step S20, carbonate minerals can be added to the dry-mix mortar. The carbonate minerals are one or more of limestone (CaCO3), magnesite (MgCO3), dolomite (CaMg(CO3)2), and siderite (FeCO3). Preferably, the particle size of the carbonate mineral is ≤0.3 mm, and the mass ratio of sulfur, cement, and carbonate minerals is (5-25):(50-90):(50-15). In addition, before adding water in step S20, pyrite can also be added to the dry-mix mortar. Preferably, the particle size of the pyrite is ≤0.3 mm, more preferably, the particle size of the pyrite is ≤0.15 mm, and the mass ratio of the pyrite to the dry-mix mortar is (5-25):100.
[0041] S30, performing a foaming treatment on the cement slurry obtained in step S20 to obtain a foamed slurry;
[0042] It should be further explained that the foaming treatment includes chemical foaming treatment or physical foaming treatment. The chemical foaming treatment uses a chemical foaming agent, wherein the chemical foaming agent is one or both of sodium percarbonate and hydrogen peroxide; the physical foaming treatment uses physical foam, wherein the physical foam is prepared by a 5% to 15% aqueous solution of a commercially available vegetable protein type foaming agent through a foaming device, and the foaming parameters in the foaming device are set to an air-water ratio of air to the vegetable protein type foaming agent aqueous solution of 1: (0.5 to 1.5);
[0043] When chemical foaming treatment is performed, the mass ratio of the chemical foaming agent used to the cement slurry is 1% to 10%. Preferably, the amount of chemical foaming agent added is 1% to 3% sodium percarbonate or 1% to 3% hydrogen peroxide or 8% to 10% sodium bicarbonate; when physical foaming treatment is performed, the amount of physical foam added per ton of cement slurry is 100 to 500 L, preferably 200 to 300 L.
[0044] S40, allowing the foaming slurry to stand and solidify at a high temperature of 40° C. to 100° C. (preferably, 60° C. to 80° C.), and curing it at the same temperature and an ambient humidity of not less than 80% (preferably, not less than 90%) for 10 to 20 days to obtain a slow-release polysulfide lightweight material.
[0045] The most commonly used sulfur / limestone autotrophic denitrification system (SLAD) in the prior art can simultaneously remove nitrogen and phosphorus from wastewater. However, sulfur itself is poorly soluble in water, and its biological utilization has certain limitations. Therefore, the denitrification and phosphorus removal effect of this system is limited, and it is difficult to meet water quality standards. In the preparation method of the present invention, sulfur, cement, and water are mixed and exposed to high temperature conditions of 40°C to 100°C. The sulfur and the alkali (i.e., calcium hydroxide) generated during the cement hydration process undergo a disproportionation reaction to form polysulfides. The reaction equation is as follows:
[0046] 3CaO·SiO2+nH2O=xCaO·SiO2·(n-3+x)H2O+(3-x)Ca(OH)2
[0047] 2CaO·SiO2+nH2O=xCaO·SiO2·(n-2+x)H2O+(2-x)Ca(OH)2
[0048] 3Ca(OH)2+xS=2CaS (x / 2-1) +CaS2O3+3H2O
[0049] Polysulfides have high solubility and are easily utilized by microorganisms, enabling a higher denitrification rate. Furthermore, the calcium hydroxide in cement reacts to produce calcium polysulfide, making calcium ions more soluble in water. The material continuously releases calcium ions, which react with phosphorus in the water to form phosphate precipitates, achieving the purpose of phosphorus removal. When the material contains pyrite, the pyrite can simultaneously play the role of autotrophic denitrification and slow-release iron ion phosphorus removal. Microorganisms oxidize the low-valent sulfur and low-valent iron in the pyrite to perform autotrophic denitrification. At the same time, the iron ions or ferrous ions produced are released into the water, reacting with phosphate to form precipitates, improving the denitrification and phosphorus removal effects. So far, no one in the field of environmental functional materials and sewage treatment has found a way to prepare slow-release polysulfide lightweight materials using this chemical reaction principle.
[0050] The slow-release polysulfide lightweight material prepared by the preparation method of the present invention has a compressive strength of 0.5-20 MPa and a density of 0.6-1.5 g / cm 3 The porosity is 20% to 70%, and the pore diameter is 0.05 to 1 mm.
[0051] The method for denitrifying and removing phosphorus from sewage using the slow-release polysulfide lightweight material comprises: filling the slow-release polysulfide lightweight material into a reactor; then inoculating the reactor with anaerobic sludge or a bacterial agent containing sulfur-containing autotrophic denitrifying bacteria to form biofilms, and starting the reactor; and introducing sewage into the reactor to carry out denitrification and phosphorus removal. In the reactor, the slow-release polysulfide lightweight material continuously releases polysulfide into the sewage, and the microorganisms utilize the polysulfide, elemental sulfur, and / or pyrite in the slow-release polysulfide lightweight material in the reactor to carry out autotrophic denitrification and denitrification. Furthermore, the slow-release polysulfide lightweight material continuously releases calcium ions and iron ions into the sewage, which react with phosphorus in the water to form phosphate precipitation for phosphorus removal.
[0052] Example 1
[0053] A method for preparing a slow-release polysulfide lightweight material according to this embodiment includes the following steps:
[0054] 150 parts of P·O 42.5 cement, 30 parts of 100-mesh sulfur powder, 10 parts of 100-mesh limestone powder, 30 parts of 100-mesh pyrrhotite powder, and 80 parts of water were weighed in a container according to the mass ratio and stirred evenly to obtain cement slurry. Then, a plant protein-type foaming agent with a mass fraction of 10% was prepared into physical foam through a foaming equipment at a gas-water ratio of 1:1. 170L of physical foam was added to each ton of cement slurry, and stirred at a speed of 2000rpm for 30s to fully mix the physical foam and the slurry. The mixture was poured into a mold and naturally solidified at 50°C. Finally, under a constant temperature of 50°C, the ambient humidity was maintained at above 90% using plastic wrap and water spraying facilities, and cured for 14 days to obtain a slow-release polysulfide lightweight material. The obtained material is as follows Figure 1 As shown in (a)-1(b), the density of the material was measured to be 1.09 g / cm 3 , porosity is about 24.6%, and compressive strength is 1.23MPa.
[0055] The above materials were crushed into particles of 1-2 cm in size using a crusher and loaded into a fluidized bed reactor with a porosity of 46.90%. Clean water was passed into the reactor with a residence time of 24 hours. The polysulfide concentration in the effluent was monitored and the rate of polysulfide release from the above materials to the outside world was calculated under these conditions. The results are as follows: Figure 2 The average polysulfide concentration in the leachate is 1.95 mmol / L, and under this condition, the average rate of polysulfide release from the slow-release polysulfide lightweight material to the outside world is 0.75 mmol / (kg·d).
[0056] Example 2
[0057] The basic content of this embodiment is the same as that of Example 1, except that: a method for preparing a slow-release polysulfide lightweight material in this embodiment includes the following steps:
[0058] 150 parts of P·O 42.5 cement, 30 parts of 100-mesh sulfur powder, 30 parts of 100-mesh pyrrhotite powder, 10 parts of 100-mesh limestone powder, and 80 parts of water were weighed and mixed in a container to produce a cement slurry. A 10% mass fraction of a plant protein-based foaming agent was then added to a foaming machine at a 1:1 air-water ratio to produce a physical foam. 165 L of physical foam was added per ton of cement slurry. The mixture was stirred at 2000 rpm for 30 seconds to thoroughly mix the physical foam and slurry. The mixture was then poured into a mold and allowed to solidify naturally at 50°C. Finally, the material was cured for 14 days at a constant temperature of 50°C, with the humidity maintained above 90% using plastic wrap and a water spray system. This yielded a slow-release polysulfide lightweight material. The material's density was measured to be 1.09 g / cm 3 , porosity is about 24.6%, and compressive strength is 1.23MPa.
[0059] The above materials were crushed into 1-2 cm particles using a crusher. This material was used as filler to construct a vertical subsurface flow artificial wetland reactor. The wetland reactor has a diameter of 30 cm, a height of 80 cm, and a porosity of 41.09%. Sulfur autotrophic denitrifying bacteria were inoculated to form biofilm for 16 days. The influent was river water with an appropriate amount of NO3 added. - -N and PO4 3- -P is configured according to the sewage discharge level B standard, with an average TON concentration of 20.05±0.98mg / L, PO4 3- The average -P concentration was 1.03±0.04 mg / L.
[0060] During the operation of the wetland, phosphorus in the effluent was completely removed at HRT 24 h, the average TON concentration was 1.08 ± 0.59 mg / L, and the average TON removal rate was 6.87 g N / (m 2 ·d); at HRT 18h, phosphorus in the effluent was completely removed, the average TON concentration was 2.02±0.38mg / L, and the average TON removal rate was 8.68g N / (m 2 ·d); at HRT 12h, phosphorus in the effluent was completely removed, the average TON concentration was 3.60±0.61mg / L, and the average TON removal rate was 11.81g N / (m 2 ·d).
[0061] Example 3
[0062] The basic content of this embodiment is the same as that of Example 1, except that: a method for preparing a slow-release polysulfide lightweight material in this embodiment includes the following steps:
[0063] 150 parts of P·O 42.5 cement, 15 parts of 100-mesh sulfur powder, 15 parts of 100-mesh pyrrhotite powder, 5 parts of 100-mesh limestone powder, and 67 parts of water were weighed and mixed in a container to produce a cement slurry. A 10% mass fraction of a plant protein-based foaming agent was then added to a foaming machine at a 1:1 air-water ratio to produce a physical foam. 200 L of physical foam was added to each ton of the mixed slurry. The mixture was stirred at 2000 rpm for 30 seconds to thoroughly mix the physical foam and slurry. The mixture was then poured into a mold and naturally solidified at 50°C. Finally, the material was cured for 14 days at a constant temperature of 50°C, with the humidity maintained above 90% using plastic wrap and a water spray system. This yielded a slow-release polysulfide lightweight material. The material's density was measured to be 0.94 g / cm 3 , porosity is about 29.60%, and compressive strength is 1.77MPa.
[0064] The above materials were crushed into 1-2 cm particle size using a crusher. This material was used as filler to construct a biofilter reactor with a diameter of 6 cm, a height of 40 cm, and a porosity of 44.12%. Sulfur autotrophic denitrifying bacteria were inoculated and biofilm was formed for 16 days. The influent was tap water prepared according to the Class B sewage discharge standard, with an average TON concentration of 21.57 ± 0.76 mg / L and PO4 3- The average concentration of -P was 1.04±0.02mg / L, and the system was operated under the condition of HRT 24h. Phosphorus in the effluent was completely removed, and the average removal rate of TON was 5.63g N / (m 2 ·d).
[0065] Example 4
[0066] The basic content of this embodiment is the same as that of Example 1, except that: a method for preparing a slow-release polysulfide lightweight material in this embodiment includes the following steps:
[0067] 150 parts of P·O 42.5 cement, 30 parts of 100-mesh sulfur powder, and 65 parts of water were weighed in a container according to the mass ratio and stirred evenly to obtain cement slurry. Then, a plant protein-based foaming agent with a mass fraction of 10% was used to prepare physical foam through a foaming device at a gas-water ratio of 1:1. 200L of physical foam was added to each ton of mixed slurry, and stirred at 2000rpm for 30s to fully mix the physical foam and slurry. The mixture was poured into a mold and naturally solidified at 60°C. Finally, under a constant temperature of 60°C, the ambient humidity was maintained above 90% using plastic wrap and water spraying facilities. After curing for 14 days, a slow-release polysulfide lightweight material was obtained. The density of the material was measured to be 0.96g / cm 3 , the porosity is about 28.57% and the compressive strength is 1.62MPa.
[0068] The above materials were crushed into 5-10 mesh size using a crusher, 10g of slow-release polysulfide lightweight material was weighed into a 60mL container, and 50mL of simulated wastewater was added. The TON concentration in the simulated wastewater was 20mg / L, PO4 3- -P concentration was 1 mg / L, 3.5 mL of 10% sulfur autotrophic denitrifying bacteria solution was added (the volume of the inoculated solution was 7% of the wastewater volume), nitrogen was blown into the mixed solution for 1 minute to remove oxygen in the solution, and the solution was sealed for denitrification and phosphorus removal. The reaction lasted for 14 days, and the nitrogen and phosphorus concentrations in the wastewater were tested on the 2nd, 4th, 6th, 8th, 10th, 12th and 14th days respectively. The PO4 3- -P was completely removed at the first sampling time point. At the end of the reaction, the TON removal rate was 83.50% and the average removal rate was 5.98 mg N / (kg·d).
[0069] Example 5
[0070] The basic content of this embodiment is the same as that of Example 1, except that: a method for preparing a slow-release polysulfide lightweight material in this embodiment includes the following steps:
[0071] 150 parts of P·O 42.5 cement, 5 parts of 100-mesh sulfur powder, 5 parts of 100-mesh limestone powder, and 58 parts of water were weighed in a container and stirred evenly to obtain a cement slurry. Then, a 10% mass fraction of a plant protein-based foaming agent was used to prepare a physical foam using a foaming device at a 1:1 gas-water ratio. 210L of physical foam was added to each ton of mixed slurry. The mixture was stirred at 2000 rpm for 30 seconds to fully mix the physical foam and slurry. The mixture was poured into a mold and naturally solidified at 40°C. Finally, under a constant temperature of 40°C, the ambient humidity was maintained above 90% using plastic wrap and water spraying facilities. The material was cured for 14 days to obtain a slow-release polysulfide lightweight material. The density of the material was measured to be 1.24g / cm 3 , porosity is about 27.3%, and compressive strength is 2.02MPa.
[0072] The material was crushed into particles of 0.2-0.5 mm using a crusher. 0.1 g of the material was then weighed into a series of 50 mL containers. 25 mL of wastewater containing 200 mg / L of phosphate was added, and the containers were placed in a constant temperature shaker. Phosphorus adsorption experiments were conducted at 25°C and 160 rpm. Residual phosphorus concentrations in the wastewater were measured at 5 minutes, 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, and 24 hours. At adsorption equilibrium, the slow-release polysulfide lightweight material achieved a saturated phosphorus adsorption capacity of 28.24 mg / g. Saturation was considered achieved when the phosphorus adsorption reached greater than 90% of the saturated capacity after 8 hours.
[0073] The above description is merely a partial embodiment of the present invention and does not constitute any formal or substantial limitation to the present invention. It should be noted that those skilled in the art may make several improvements and additions without departing from the method of the present invention, and such improvements and additions shall also be considered within the scope of protection of the present invention. Furthermore, any structural methods and embodiments similar to the technical solution devised without creative design without departing from the purpose of the present invention shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a slow-release polysulfide lightweight material, characterized in that: The method comprises mixing sulfur and cement to obtain dry-mix mortar; then adding water to the dry-mix mortar, stirring to obtain cement slurry, and foaming the cement slurry to obtain foamed slurry; allowing the foamed slurry to stand and solidify under high temperature conditions, and curing under the same temperature conditions to obtain a slow-release polysulfide lightweight material; wherein the high temperature conditions are 40°C to 100°C, the mass ratio of the dry-mix mortar to water is 1: (0.3-0.6), and the mass ratio of sulfur to cement is (5-25): (50-90).
2. The method for preparing a slow-release polysulfide lightweight material according to claim 1, characterized in that: The curing time is 10 to 20 days.
3. The method for preparing a slow-release polysulfide lightweight material according to claim 1, characterized in that: The particle size of the sulfur is ≤0.3 mm.
4. The method for preparing a slow-release polysulfide lightweight material according to claim 1, wherein: The foaming treatment includes chemical foaming treatment or physical foaming treatment. The chemical foaming treatment uses a chemical foaming agent, wherein the chemical foaming agent is one or both of sodium percarbonate and hydrogen peroxide; the physical foaming treatment uses physical foam, wherein the physical foam is prepared by a 5% to 15% vegetable protein type foaming agent aqueous solution through a foaming device, and the foaming parameters in the foaming device are set to an air-water ratio of air to the vegetable protein type foaming agent aqueous solution of 1: (0.5 to 1.5).
5. The method for preparing a slow-release polysulfide lightweight material according to claim 4, characterized in that: When chemical foaming treatment is performed, the mass ratio of the chemical foaming agent used to the cement slurry is 1%~10%; when physical foaming treatment is performed, the amount of physical foam added per ton of cement slurry is 100~500 L.
6. A method for preparing a slow-release polysulfide lightweight material according to any one of claims 1 to 5, characterized in that: The method comprises adding carbonate minerals to the dry mortar before adding water, wherein the mass ratio of sulfur, cement and carbonate minerals is (5-25): (50-90): (50-15).
7. The method for preparing a slow-release polysulfide lightweight material according to claim 6, characterized in that: The method further includes adding pyrite to the dry-mix mortar before adding water, wherein the mass ratio of the pyrite to the dry-mix mortar is (5-25):
100.
8. A slow-release polysulfide lightweight material, characterized by: The method according to any one of claims 1 to 7 is used to prepare the slow-release polysulfide lightweight material, wherein the compressive strength of the slow-release polysulfide lightweight material is 0.5-20 MPa, the density is 0.6-1.5 g / cm³, the porosity is 20%-70%, and the pore diameter is 0.05-1 mm.
9. A method for denitrification and dephosphorization of sewage using the slow-release polysulfide lightweight material according to claim 8, characterized in that: The slow-release polysulfide lightweight material is filled into a reactor, and microorganisms are inoculated to form biofilms. After biofilm formation is completed, sewage is introduced into the reactor to perform nitrogen and phosphorus removal treatment.
Citation Information
Patent Citations
An autotrophic denitrification biological filter with coupled packing and its application
CN109052641B
A lightweight slow-release nitrogen and phosphorus removal material, its preparation method and application
CN110002806B
Simultaneous phosphorus and nitrogen removal light material, preparation method and application thereof
CN110078221A
Synchronous denitrification and phosphorus removal composite filler and preparation method and application thereof
CN110683631A